FORMULASI SHAMPO KRIM CAIR DARI KOMBINASI EKSTRAK DAUN WARU (Hibiscus tiliaceus L.) DAN SARI BUAH JERUK NIPIS (Citrus aurantifolia Swingle.) - Mirawati Mirawati (Fakultas Farmasi UMI, 2012)
Leaves of hibiscus (Hibiscus tiliaceus L.) is widely used by communities to nourish the hair while the juice of lime (Citrus aurantifolia Swingle.) used to eliminate dandruff. Its use is directly less practical than if formulated in the form of shampoo. Cream shampoo formulation development using emulgator sodium lauryl sulfate and sodium hydroxide-coconut oil and the carbopol with concentration 0.1% 0.3% and 0.5%. This study aims to determine the formula that has the most optimal stability. The evaluation was done by testing the stability of organoleptis, homogeneity, determination of pH, type of emulsion, creaming volume, viscosity and size of the dispersed drops before and after accelerated storage. The results show the entire formula is stable because it does not experience phase separation, but the formula that stability is the most optimal use of sodium lauryl sulfate emulgator and karbopol with a concentration of 0.1% because it has a different viscosity and yield value are not significant (α = 0.5). Keywords: Leaf Hibiscus, Lemon, Cream Shampoo, Stability